STRATEGIES IN REDUCING TURNOVER INTENTION INFLUENCED BY ORGANIZATIONAL COMMITMENT, ORGANIZATIONAL CLIMATE, AND INTERPERSONAL RELATIONSHIPS - Nugroho, Novianto Eko (Universitas Madura, 2024)
Leasing companies often face various challenges that can affect their performance and operational sustainability. One of the main issues faced is the high level of turnover intention among employees. Turnover intention refers to an employee's desire to leave the company and seek employment elsewhere. This study aims to examine the effect of organizational commitment, organizational climate, and interpersonal relationships on turnover intention.